2019
DOI: 10.2478/pjst-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Soccer Referees: A Narrative Review

Abstract: Introduction. The heightened physical exertion stemming from greater physical loads in football matches has elicited greater development of physical conditioning in both players and referees.Material and methods. The current study consisted of a meta-analysis geared towards identifying the scientific data currently available on the training of referees.Results. With respect to the characterization of the training of football referees, the results of this study showed that there is a diversity of both its metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The fact behind that may be as national-level referees are more experienced [15], they have greater opportunity to conduct more matches than state level referees and assessors" assessment of each national level matches help them to grow more confidence and managing capacity of stress and anxiety at pre, during and postmatch circumstances [28]. Scientists found that referees and assistant referees are submitted to high physical and mental stress during matches [9,25,29]. Referees suffering from severe injuries were nearly three times more likely to report symptoms of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The fact behind that may be as national-level referees are more experienced [15], they have greater opportunity to conduct more matches than state level referees and assessors" assessment of each national level matches help them to grow more confidence and managing capacity of stress and anxiety at pre, during and postmatch circumstances [28]. Scientists found that referees and assistant referees are submitted to high physical and mental stress during matches [9,25,29]. Referees suffering from severe injuries were nearly three times more likely to report symptoms of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Coaches and parents are widely analysed and discussed societal groups. In contrast, the referee has been often overlooked (Andersson, 2019;Cipriano et al, 2020). This may be due to the various roles of referees in different sports (MacMahon et al, 2015).…”
Section: Authors' Contributionmentioning
confidence: 99%
“…Additionally, studies indicate a correlation between perceived stress and physiological reactions, such as changes in heart rate (Castillo-Rodríguez et al, 2021), suggesting that referees with a better control of their stress tend to experience less physiological reactions and show better performance. Studies on referees' emotions and performance are, however, somewhat limited (Cipriano et al, 2019), since they do not seek to understand the psychological mechanisms that explain how stress relates to emotions and performance.…”
Section: Introductionmentioning
confidence: 99%